Dances : a novel - Cuffy, Nicole (One World, 2023)
Promoted to principal dancer at the New York City Ballet, Cece Cordell, a young black woman, still feels like she doesn't belong, and, despite her dream achievement, is faced with a choice that may derail her career, sending her on a pilgrimage to find her missing older brother and reclaim the parts of herself lost in the pursuit of her art.